Update on Clinical Inflammometry for the Management of Airway Diseases - Parameswaran Nair (Canadian Respiratory Journal)
Airway inflammation is a central feature of many airway diseases such as asthma, chronic bronchitis, bronchiectasis and chronic cough; therefore, it is only logical that it is measured to optimize its treatment. However, most treatment recommendations, including the use of anti-inflammatory therapies such as corticosteroids, are based on assessments of only airflow and symptoms. Over the past 10 years, methods have been developed to assess airway inflammation relatively noninvasively. Quantitative cell counts in sputum and the fraction of exhaled nitric oxide are the most validated tests. Judicious use of currently available drugs, such as corticosteroids, bronchodilators and antibiotics, and other anti-inflammatory therapies guided by sputum eosinophil and neutrophil counts, have been demonstrated to decrease exacerbations of asthma and chronic obstructive pulmonary disease, ameliorate cough, improve quality of life in patients with these diseases and is cost effective compared with treatment strategies based on guidelines that do not incorporate these measurements. Thus, it is unfortunate that this is not used more widely in the management of airway diseases, particularly in patients with severe asthma and chronic obstructive pulmonary disease who experience frequent exacerbations.